Recent Progress on Immunotherapy for Breast Cancer: Tumor Microenvironment, Nanotechnology and More - Li, Yang; Miao, Wenfang; He, Doudou; Wang, Siqi; Lou, Jianjuan; Jiang, Yanni; Wang, Shouju (Frontiers in Bioengineering and Biotechnology, 2021)
Immunotherapy is a major emerging treatment for breast cancer (BC). However, not all breast cancer patients derive benefit from immunotherapy. Predictive biomarkers of immunotherapy, such as tumor mutation burden and tumor-infiltrating lymphocytes, are promising to stratify the patients with BC and optimize the therapeutic effect. Various targets of the immune response pathway have also been explored to expand the modalities of immunotherapy. The use of nanotechnology for the imaging of predictive biomarkers and the combination with other therapeutic modalities presents a number of advantages for the immunotherapy of BC. In this review, we summary the emerging therapeutic modalities of immunotherapy, present prominent examples of immunotherapy in BC, and discuss the future opportunity of nanotechnology in the immunotherapy of BC.